Performance analysis of mobile financial industries: a comparative analysis between bKash Limited and Dutch Bangla Bank Rocket - Ahmed, Lubna (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.